Effective video learning: the theory of exceptional demand / Hafisah Yaakob - Yaakob, Hafisah; Daud, Siti Rohana; Jogeran, Jumaelya; Othman, Suzzana; Suhaime, Intan Liana; Sehat, Nani Shuhada (2021)
When the WHO declared the world facing the COVID19 pandemic in March 2020, most work routines changed digitally. Since then, educational institutions have shifted to online learning methods and digitized teaching material to replace face-to-face methods. This study aims to identify the effectiveness of the teaching video entitled Exceptional Demand as a teaching aid for lecturers who teach Microeconomics courses, especially in UiTM. The video is created and developed to fit with diploma students in which simple language and attractive animation. It makes it easier for students to understand that theory more easily and easier for lecturers to explain. Besides, the video is accessible because it was uploaded to the lecturer's YouTube channel and is appropriate with the online learning method. The objective of creating this video is; i) to make the topic of economics easier and understandable and ii) to make it fun, reachable, interesting, interactive, and easy to access via the use of technology and online applications. This video received 325 views after being published, with 31.3 percent of the viewers being male and 68.8 percent being female. Out of a total of 325 views, a total of 180 people liked this video. It was received a total of 3.8 hours of watch time, with an average of 0:42 minutes spent by each viewer. This finding will guide the other lecturers on how to create an effective video as a teaching aid. Additionally, this method is in line to support the IR 4.0 technology era.